Comparative Analysis of ChatGPT and Human Expertise in Diagnosing Primary Liver Carcinoma: A Focus on Gross Morphology - Prakasit Sa-ngiamwibool; Thiyaphat Laohawetwanit (Siriraj Medical Journal)
Objective: This study aims to compare the diagnostic accuracy of customized ChatGPT and human experts in identifying primary liver carcinoma using gross morphology.